Potency of Ethanol Extract Celery (Apium graveolens L.) Stalk as Anti-Cholesterol - I Made Subhawa Harsa; Andiani Andiani; Harsono Wiradinata; Putu Oky Ari Tania (Universitas Wijaya Kusuma Surabaya, 2022)
Increasing levels of blood cholesterol is one of the risk factors for atherosclerosis. Currently, experts have been trying used herbal medicine as an alternative treatment of atherosclerosis. One of the highlights is the use of celery stalks. Celery is generally used as a flavouring dish. In addition, celery stalks are believed able to reduce cholesterol levels because they contain flavonoids, tannins, and saponins. This study was aim to determine the effect of celery stalk ethanol extract to reduce LDL an increase of HDL level in rats after fed high-fat diet. Randomized Post Test Only Control Group Design was used to measure the HDL and LDL blood serum levels of male Wistar (Rattus norvegicus) rats fed a high-fat diet. This study was used 27 male Wistar rats (Rattus norvegicus) divided into 3 groups; K1 was only given regular feed and water, K2 was given a high-fat diet and water, K3 was given a high-fat diet and celery stalk extract at a dose of 75mg/kg BW/day for 14 days. The data were analysed by ANOVA test and Tukey HSD test. The results of the ANOVA test showed a significance value of p-value of LDL = 0.000 and HDL p-value = 0.536. Celery stalk extract (Apium graviolens L) had an effect on decreasing LDL levels but not on increasing HDL blood serum levels of white Wistar rats (Rattus norvegicus) given high-fat diet.